Driving business intelligence transformation through AI and data analytics: a comprehensive framework - Perumal, Thinagaran; Chetlapalli, Himabindu (Nisaab Publishers, 2024)
The integration of data analytics and artificial intelligence (AI) is causing a significant shift in the transformation of business intelligence (BI). With an emphasis on utilising AI and data analytics to propel corporate success, this paper offers a thorough framework intended to assist organisations through this transition. Crucial components covered by the framework include data gathering, modelling, preprocessing, analysis, and visualisation. It also draws attention to the difficulties that businesses encounter, such as those related to hiring qualified staff, ethical dilemmas, and regulatory compliance. This study intends to give firms concrete solutions to improve decision-making, optimise business intelligence (BI) operations, and achieve a competitive edge in a data-driven world. It does this by synthesising insights from expert consultations, empirical research, and literature.